SPATIAL ANALYSIS AND ENVIRONMENTAL FACTORS ASSOCIATED AGAINST CASE OF DENGUE HEMORRHAGIC FEVER (DHF) IN LIMBOTO DISTRICT, GORONTALO - Ririn Pakaya (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Dengue Hemorrhagic Fever (DHF) was a disease caused by dengue virus. DHF transmitted by mosquito bites from Aedes genus, mainly Aedes aegypti and Aedes albopictus. DHF was emerging over the year and attacking all of age groups.  It was related to the environmental condition and community behavior. Until now, the Incidence Rate (IR) of DHF from 1968  was increased. Mortality caused byDHF was categorized as high if CFR more than 2%. Therefore, there were  5  provinces that  categorizedon  high  CFR  in  2014  such  as  Bengkulu, Bangka  Belitung Archipelago, South Borneo, Gorontalo and Maluku. Gorontalo Province consisted of 5 regencies and Gorontalo Regencies increased dengue cases significantly, especially Limboto District i.e., 35 cases in 2012, 49 cases in 2013, 34 cases in 2014, and 40 cases by 2015 by 8 endemic counties. Objective of this study was to understand spatial distribution of DHF cases and analysis environment factor against cases of DHF in Limboto District. The method ofstudy was observational used cross sectional study design supported by Geographic Information System (GIS) for spatial information. Main result by Poisson‟s regression test showed that the environmental variables for instance precipitation, temperature, humidity, and wind  speed with DHF occurrence.   Correlation analysis  of   environmental variables to DHF cases showed that only the humidity in the previous two months (lag2) (P = 0.01) had a significant but negative correlation with DHF cases.  Keyword: DHF cases, Precipitation, Temperature, Humidity, Wind Speed